2011
DOI: 10.1016/j.gca.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

An improved description of the interactions between rare earth elements and humic acids by modeling: PHREEQC-Model VI coupling

Abstract: The Humic Ion Binding Model VI (Model VI) -previously used to model the equilibrium binding of rare earth elements (REE) by humic acid (HA) -was modified to account for differences in the REE constant patterns of the HA carboxylic and phenolic groups, and introduced into PHREEQC to calculate the REE speciation on the HA binding sites. The modifications were shown to greatly improve the modeling. They allow for the first time to both satisfactorily and simultaneously model a large set of multi-REE experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 44 publications
7
96
0
Order By: Relevance
“…MREE enrichment onto biological surfaces is also consistent with previous studies that demonstrate a large MREE affinity of bacterial colonies and/or humate and fulvate natural polymers to biological surfaces (Takahashi et al, 2005(Takahashi et al, , 2007. This affinity is apparently driven by the capability of some binding tags to extract REE from the aqueous phase (Marsac et al, 2011;Martinez et al, 2014;Park et al, 2016 and references therein).…”
Section: Discussionsupporting
confidence: 90%
“…MREE enrichment onto biological surfaces is also consistent with previous studies that demonstrate a large MREE affinity of bacterial colonies and/or humate and fulvate natural polymers to biological surfaces (Takahashi et al, 2005(Takahashi et al, , 2007. This affinity is apparently driven by the capability of some binding tags to extract REE from the aqueous phase (Marsac et al, 2011;Martinez et al, 2014;Park et al, 2016 and references therein).…”
Section: Discussionsupporting
confidence: 90%
“…Same results were obtained by Stolpe et al (2013) using FFF separation for Alaskan rivers water samples. This strong binding of REE by organic matter was confirmed by several field, experimental and modeling studies (Tang and Johannesson 2003;Johannesson et al 2004;Sonke and Salters 2006;Pourret et al 2007a, b;Stern et al 2007;Pédrot et al 2008;Kerr et al 2008;Marsac et al 2011). Moreover, Davranche et al (2011) demonstrated that Fe occurs mainly in wetland soils as amorphous Fe(III)-nanoparticles embedded within the organic matter which are poor in REE and trace elements.…”
Section: Colloidal Controlmentioning
confidence: 69%
“…or the precipitation of LREE and HREE with phosphates (e.g., Johannesson and Lyons 1995;Byrne et al 1996;Taunton et al 2000). However, more recent studies have demonstrated that in organic-rich waters in which REE speciation is dominated by their binding with organic molecules, the REE pattern is controlled by the surface properties of the organic matter itself (e.g., Pourret et al 2007b;Kautenburger 2009;Marsac et al 2010Marsac et al , 2011Kautenburger et al 2014).…”
Section: Factor Controlling the Ree Pattern Variability In Wetland Watermentioning
confidence: 99%
See 2 more Smart Citations